Modeling and simulation of doubly fed induction generator for wind turbine - Hussin, Mohamed Saiful Firdaus; Mohd Yassim, Halyani; Ahmad, Emy Zairah; Idris, Norain; Zakaria, Muhammad Zulfattah (Asian Research Publishing Network (ARPN), 2016)
The construction of modern wind turbine is costly, complex and risky. In this paper, modeling and simulation of doubly fed induction generator (DFIG) for wind turbine is presented to investigate the dynamic behavior of the system. The behavior of the system is described in mathematical equations, modeled and simulated in MATLAB/Simulink using field orientation principle. Simulation results are presented in two operation modes namely below and above synchronous speed. Measurement obtained from 5 MW wind turbine confirmed the theoretical result. The created modeled can be used to simulate the behavior of DFIG for wind turbine inexpensively, efficiently and safely.